2004
DOI: 10.1016/j.amjhyper.2004.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Fractional diastolic and systolic pressure in the ascending aorta are related to the extent of coronary artery disease

Abstract: Pulse pressure (PP), FSP, and FDP of the ascending aorta are related to the risk of three-vessel disease in patients with coronary artery disease and preserved left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 18 publications
3
23
1
2
Order By: Relevance
“…The major hemodynamic finding of our study was that in patients with CAS, PP was markedly increased not only in the ascending aorta 16 but also in the abdominal aorta at the level of renal arteries. PP amplification was mainly due to a slight increase in SBP along the aorta, in association with a consistently lowered DBP, which was around a value of 70 mm Hg.…”
Section: Aortic Pp Amplificationmentioning
confidence: 63%
“…The major hemodynamic finding of our study was that in patients with CAS, PP was markedly increased not only in the ascending aorta 16 but also in the abdominal aorta at the level of renal arteries. PP amplification was mainly due to a slight increase in SBP along the aorta, in association with a consistently lowered DBP, which was around a value of 70 mm Hg.…”
Section: Aortic Pp Amplificationmentioning
confidence: 63%
“…Most studies [33][34][35] other than one [36] found centrally measured aortic pulse pressure or carotid pressure rather than brachial pulse pressure to correlate with CAD. The present study takes this analysis a stage further relating brachial pulse pressure to total but primarily non-obstructive, atheroma, determined non-invasively in asymptomatic patients with diabetes mellitus, while in keeping with most previous studies finding no correlation between brachial pulse pressure and obstructive coronary disease.…”
Section: Pulse Pressure As a Predictor Of Coronary Arterial Atheromamentioning
confidence: 96%
“…The use of a high-fidelity pressure transducer could increase the accuracy of the recorded pressure waveform. However, the fluid-filled system has been used commonly in clinical studies (16,41,42). In clinical practice, access to a high-fidelity pressure transducer is limited, and use of such a system requires additional procedures that prolong the already invasive measurement.…”
Section: Discussionmentioning
confidence: 99%